Isotopic signature of the caridean shrimp Potimirim brasiliana Villalobos, 1960 in different points of a pristine area in southeastern Brazil - Teles, Jeniffer Natalia; França, Nielson Felix Caetano; Pantaleão, João Alberto Farinelli; Santos, Rafael Carvalho [UNESP]; Pardo, Luis Miguel; Mantelatto, Fernando Luis (FapUNIFESP (SciELO), 2023)
Aim: The aim of this study was to investigate the isotopic signature of P. brasiliana captured in three different points along the river flow toward the sea of the Prumirim River, northern coast of the state of São Paulo/Brazil in order to test the hypothesis of similarity between isotopic signature of individuals living in separated areas of the river. Methods: We used stable isotope analyses (δ13C and δ15N) at three points of the river and ANOVA and Bayesian Ellipses analyses were performed. Results: Our results showed that are a differential isotopic enrichment along the river course in13C, providing important results on the environmental condition and anthropogenic impacts in the region. In addition, the food biology of P. brasiliana was characterized as a primary consumer corroborating with the detritivores feeding habit observed in previous studies of stomach content analysis. Conclusions: Our research, limited to a single area along the northern coast of the state of São Paulo, uncovers intriguing findings that merit replication in other areas within the region. This is particularly crucial given the rising number of anthropogenic influences resulting from urban development, underscoring the need for improved monitoring of these areas.
Assinatura isotópica do camarão carídeo Potimirim brasiliana Villalobos, 1960 em diferentes pontos de uma área preservada no sudeste do Brasil
Keywords: amphidromous species; Atyidae; conservation; freshwater shrimp; stable isotopes